Lily and the octopus [large type] - Rowley, Steven, 1971- (Thorndike Press, A part of Gale, Cengage Learning, 2016)
"This is a story about that special someone: the one you trust, the one you can't live without. For Ted Flask, that someone special is his aging companion Lily, who happens to be a dog. Lily and the Octopus reminds us how it feels to love fiercely, how difficult it can be to let go, and how the fight for those we love is the greatest fight of all" --